ShellBank: traceability toolkit and global database of marine turtle DNA - Michael P. Jensen; Greta J. Frankham; Carla Alonso O’Friel; Erin L. LaCasella; Kelly I. Morgan; Maftuna Sola; Lucy M. I. Webster; Peter H. Dutton; Christine A. Madden (Frontiers in Marine Science, 2026)
Effective conservation and enforcement strategies for marine turtles depend on understanding population structure, connectivity, and the geographic origins of turtles impacted by threats such as bycatch, overexploitation, and illegal trade. However, mitochondrial DNA (mtDNA) data remain fragmented across studies, with inconsistent sequence lengths, haplotype nomenclature, and metadata standards limiting their application in conservation, management, and wildlife forensics. To address these challenges, we developed ShellBank, a global marine turtle genetic traceability toolkit and open-access mtDNA database that consolidates and standardizes more than 20,000 mtDNA control-region sequences from published literature and verified contributed datasets. The platform harmonizes sequence lengths, haplotype nomenclature, and associated metadata, and provides tools to search haplotypes, access population-level baselines, extract frequency tables for Mixed Stock Analysis (MSA), and explore connectivity among nesting, in-water, and trade datasets. We demonstrate its utility through two case studies. First, mtDNA from a tortoiseshell seizure in the United Kingdom was compared against the ShellBank baseline, identifying likely source rookeries in the Eastern Caribbean and highlighting priority sampling gaps. Second, reanalysis of a hawksbill turtle foraging aggregation on the Great Barrier Reef using an expanded reference baseline substantially altered previous stock assignment estimates, corroborated flipper-tag and satellite-tracking data, and confirmed multi-stock connectivity across the western Pacific. By centralizing and standardizing global marine turtle mtDNA data, ShellBank improves the resolution, accuracy, transparency, and application of genetic traceability for conservation, management, and enforcement, strengthening the ability of researchers, managers, decision-makers, and enforcement agencies to identify source regions, detect population-level impacts, understand ecological connectivity, and guide evidence-based conservation actions.

Mycobacterium gordonae (Actinomycetota: Mycobacteriales: Mycobacteriaceae) Infecting Captive‐Reared Laurel Dace, Chrosomus saylori (Cypriniformes: Leuciscidae) in North America - Daniel Gordillo‐González; Steven P. Ksepka; Haley R. Dutton; Kamila Cajiao‐Mora; John H. Brule; Bernard R. Kuhajda; Anna L. George; Stephen A. Bullard (Journal of Fish Diseases, 2026)
A captive‐reared cohort of Laurel Dace, Chrosomus saylori (Skelton 2001) (Cypriniformes: Leuciscidae), a federally‐endangered species endemic to several streams in eastern Tennessee's Cumberland Plateau, exhibited signs of morbidity and trickling mortalities in a recirculating aquaculture system. Ziehl‐Neelsen (ZN) staining revealed acid‐fast rod‐shaped bacteria within necrotic and intracellular lesions affecting the eye, swim bladder, spleen, and ovary. Histopathology showed granulomatous inflammation characterised by macrophages, multinucleated giant cells, and eosinophilic exudates. The eye, swim bladder, and ovary were particularly impacted: the choroid plexus of the eye displayed haemorrhages and dense cellular infiltrates; the swim bladder exhibited granulomatous inflammation with extensive fibrosis; the ovary contained caseous granulomas; and the choroid plexus of the eye displayed haemorrhages and dense cellular infiltrates. PCR amplification of the hsp65 gene (316 bp) from formalin‐fixed and paraffin‐embedded lesioned tissues was identical (100% similar; 424 bp fragment) to that of the type strain of Mycobacterium gordonae Bojalil et al. 1962 (AF547840). This is the first report of an infection by M. gordonae in Laurel Dace; the first record of this bacterium causing a lesion in the swim bladder, eye, or ovary; and the first record of M. gordonae from a freshwater fish in North America.

Blood biomarker changes and relationships after low dose oral ketamine treatment for post-traumatic stress disorder (PTSD) - Bonnie L. Quigley; Emerald Orr; Sophie Kafka; Maryam Hajishafiee; Ana P. Bouças; Nathan Wellington; Megan Dutton; Monique Jones; Fiona Randall; Jim Lagopoulos; Adem T. Can; Daniel F. Hermens (Psychopharmacology, 2026)
Rational Ketamine has been investigated as a treatment alternative for PTSD for the last 20 years, yet there have been limited reports of biological changes or biomarker characterisation related to treatment. Objectives To address this significant gap, this study analysed blood samples from 25 participants with PTSD who took part in an open-label 6-week trial of low dose oral ketamine treatment. Methods Serum and plasma samples were quantified before and after ketamine treatment for brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor A (VEGF-A), serotonin, FK506 binding protein 51 (FKBP51) and a panel of cytokines (interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-12p70, IL-17 A and tumour necrosis factor alpha (TNFα)). Results Analysis of BDNF and VEGF-A levels from serum detected a significant positive correlation between the two biomarkers and a small but statistically significant decrease in both measures after ketamine treatment. This novel finding reinforces theories that ketamine’s effects may rely on a reciprocal interaction between BDNF and VEGF-A, offering potential insights into a biological mechanism underpinning PTSD symptom reduction. Additionally, the analysis of FKBP51 and serotonin revealed novel relationships between these biomarkers and clinical scales, before and after ketamine treatment. Finally, significant changes or relationships involving the immune cytokines were not detected, possibly because half the participants presented with low-grade inflammation while the other half did not. Conclusions This study represents a much-needed broad analysis of blood biomarkers before and after ketamine treatment for PTSD and reveals important biological changes and relationships related to this treatment.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Expanding the boundaries: regional connectivity in green turtle (Chelonia mydas) populations across Micronesia - Michael P. Jensen; Erin L. LaCasella; Donald R. Kobayashi; Amy Frey; Tammy M. Summers; Jessy R. Hapdei; George H. Balazs; Shawn K. K. Murakawa; T. Todd Jones; Summer L. Martin; Alexander R. Gaos; Peter H. Dutton (Frontiers in Marine Science, 2025)
The importance of ocean currents in influencing the connectivity and dispersal of marine megafauna, including sea turtles, is becoming increasingly recognized. However, more comprehensive studies are needed on how these currents impact the genetic makeup and connectivity of green turtle Chelonia mydas (Linnaeus, 1758) populations in the Pacific Islands region. To address this gap, our study conducted genetic analyses of green turtles in foraging grounds from four Micronesian sites and predictive modelling of hatchling dispersal patterns based on ocean currents to explore connectivity between foraging grounds and rookeries across Micronesia. We analyzed mitochondrial DNA (mtDNA) haplotype frequencies from newly collected and published data. We used Bayesian mixed stock analysis (MSA) to estimate the relative proportion of turtles from different Management Units (MUs) within the foraging grounds. Our ocean current simulations predicted hatchling dispersal trajectories, revealing how passive drift may facilitate wide-ranging dispersal and connectivity among distant foraging and nesting sites. Across the four Micronesian foraging grounds, the MSA revealed varying contributions from different rookeries, with some turtles exhibiting rare, long-distance dispersal traits. Our study highlights the intricate relationship between oceanic currents and the spatial dynamics of green turtles across the Pacific. Our findings offer essential insights into the conservation and management of green turtles by highlighting the role of oceanic currents in shaping population connectivity. Future research should focus on expanding genetic analyses and refining ocean drift simulations to enhance our understanding of marine megafauna migration and inform regional conservation strategies effectively.

Whole mitochondrial DNA sequencing improves resolution of population structure for Pacific green turtles (Chelonia mydas) - Amy Frey; Erin L. LaCasella; Michael P. Jensen; Peter H. Dutton (Frontiers in Marine Science, 2025)
Mitochondrial DNA (mtDNA) analysis is a key tool for defining population structure in marine turtles, due to their strong natal homing behavior, which leads to genetic differentiation among rookeries. However, the widespread occurrence of common haplotypes across large geographic areas, has limited the ability to resolve fine-scale population structure, particularly in the western Pacific. Understanding these population dynamics is crucial for effective conservation and management, as distinct nesting populations may face different threats. This study evaluates the use of whole mitochondrial genome sequencing to improve genetic resolution of population structure and enhance the accuracy of mixed stock analysis (MSA). We analyzed 197 nesting green turtles from six Pacific rookeries, representing two common mtDNA haplotypes (CmP20.1 and CmP22.1). Using mitochondrial capture enrichment and MSA simulations, we detected significant genetic differentiation between the rookeries in Guam and the Commonwealth of the Northern Mariana Islands (CNMI), which were previously considered a single genetic stock based on traditional control region sequencing. Our findings demonstrate that whole mitochondrial genome sequencing enhances stock resolution, improves the accuracy of MSA, and strengthens the ability to determine connectivity between nesting and foraging populations throughout the region. Refining genetics baselines using whole mitogenome sequencing will support more precise conservation strategies, allowing for targeted protection of genetically distinct populations, improved assessments of bycatch impacts, and better-informed management of critical foraging and nesting habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mitochondrial DNA Profiling to Combat the Illegal Trade in Tortoiseshell Products - Erin L. LaCasella; Michael P. Jensen; Christine A. Madden Hof; Ian P. Bell; Amy Frey; Peter H. Dutton (Frontiers in Marine Science, 2021)
Hawksbill turtles ( Eretmochelys imbricata ) are exploited for their beautiful shell known as tortoiseshell or bekko, making them extremely vulnerable in the illegal global trade of tortoiseshell products. In this study, we developed an effective, standardized method using a commercially available kit to extract DNA and obtain informative mitochondrial DNA (mtDNA) control region sequences (~800 bp) from hawksbill turtle products in order to trace the sample back to a likely stock origin. We also sequenced additional skin samples from nesting beaches of Milman Island, Australia and Arnavon Island, Solomon Islands to add to the baseline data for hawksbill turtles in the Indo-Pacific. Our results indicate that nine of the 13 tortoiseshell products obtained from Papua New Guinea and Solomon Islands were from turtles with haplotypes found primarily at the Solomon Islands rookery and did not match those from nesting populations in Australia or SE Asia, with the exception of one haplotype also found in 3% of turtles at Milman Island. We also found that 23% of the market samples have haplotypes only documented in foraging populations, which illustrates the urgent need for more extensive sampling of rookeries to fill gaps in the reference baseline database. Nevertheless, our study results demonstrate an effective methodology for obtaining DNA of sufficient quantity and quality from hawksbill turtle products.

An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.

Using mixed stock analysis to assess source populations for at‐sea bycaught juvenile and adult loggerhead turtles ( Caretta caretta ) in the north‐west Atlantic - Kelly R. Stewart; Erin L. LaCasella; Michael P. Jensen; Sheryan P. Epperly; Heather L. Haas; Lesley W. Stokes; Peter H. Dutton (Fish and Fisheries, 2019)
Assessments of fisheries by‐catch on marine megafauna are important for developing effective management strategies. For sea turtles, impacts may be evident in nesting population trends, but generally only after a lag, as turtles are slow to mature. We examined 850 loggerhead turtle ( Caretta caretta ) by‐catch samples collected over 14 years throughout the western North Atlantic to identify source nesting populations. We identified proportions of turtles from 19 distinct management units ( MU s), using mitochondrial DNA and mixed stock analysis, considering population size. We found a significant split in the distribution of small versus large loggerheads to the north and south of Cape Hatteras, North Carolina (latitude 35°N). North of Cape Hatteras, large turtles came from south‐east Florida ( SEFL ; 44% ± 15%) and the northern United States (33% ± 16%) MU s, while south of Cape Hatteras, the major contributors were Central East Florida (52% ± 20%) and south‐east Florida ( SEFL ; 41% ± 20%). Small turtles in the north came from Central East Florida (64% ± 14%), and in the south, south‐east Florida had the highest representation (56% ± 25%). There was little contribution from Mediterranean and Cape Verde populations, indicating low risk from western North Atlantic by‐catch to MUs in the Mediterranean. Understanding where threats may impact source populations is important, particularly for larger size turtles, as these individuals have the highest reproductive value. These findings allow more informed threat assessments to be conducted for loggerhead turtles considering spatial and demographic structure.

Stable carbon isotopes (δ13C) of total organic carbon and long-chain n-alkanes as proxies for climate and environmental change in a sediment core from Lake Petén-Itzá, Guatemala - Jennifer L. Mays; Mark Brenner; Jason H. Curtis; Kathryn V. Curtis; David A. Hodell; Alex Correa-Metrio; Jaime Escobar; Andrea L. Dutton; Andrew R. Zimmerman; Thomas P. Guilderson (Journal of Paleolimnology, 2017)

Diseases of captive yellow seahorse Hippocampus kuda B leeker, pot‐bellied seahorse Hippocampus abdominalis L esson and weedy seadragon Phyllopteryx taeniolatus ( L acépède) - V LePage; J Young; C J Dutton; G Crawshaw; J A Paré; M Kummrow; D J McLelland; P Huber; K Young; S Russell; L Al‐Hussinee; J S Lumsden (Journal of Fish Diseases, 2015)
Seahorses, pipefish and seadragons are fish of the F amily S yngnathidae. From 1998 to 2010, 172 syngnathid cases from the T oronto Z oo were submitted for post‐mortem diagnostics and retrospectively examined. Among the submitted species were yellow seahorses Hippocampus kuda Bleeker ( n = 133), pot‐bellied seahorses Hippocampus abdominalis Lesson ( n = 35) and weedy seadragons Phyllopteryx taeniolatus ( L acépède; n = 4). The three most common causes of morbidity and mortality in this population were bacterial dermatitis, bilaterally symmetrical myopathy and mycobacteriosis, accounting for 24%, 17% and 15% of cases, respectively. Inflammatory processes were the most common diagnoses, present in 117 cases. Seven neoplasms were diagnosed, environmental aetiologies were identified in 46 cases, and two congenital defects were identified.

Intra-community spatial variation of size-fractionated organic compounds in Long Beach, California - Margaret A. Krudysz; Steven J. Dutton; Gregory L. Brinkman; Michael P. Hannigan; Philip M. Fine; Constantinos Sioutas; John R. Froines (Air Quality, Atmosphere & Health, 2009)

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)

Biological electron tunneling through native protein media - C. C. Moser; C. C. Page; X. Chen; P. L. Dutton (JBIC Journal of Biological Inorganic Chemistry, 1997)